Influence of Pixel Design on Charge Transfer in Pinned Photodiode CMOS Image Sensors. Issue 1 (1st January 2023) - Liu, Lu; Yang, Shaohua; Yan, Ming; Li, Binkang; Guo, Yang; Guo, Mingan; Li, Gang; Zhou, Errui
Abstract: The influence of pixel design on charge transfer, mainly on potential barrier and potential pocket, is investigated in this paper. By simplifying the interface region between the pinned photodiode (PPD) and the transfer gate (TG), an intuitive and simple method for analyzing the potential barrier and pocket is presented. Through TCAD simulations, the validity of the analysis method is verified, and the influence of some key dimension and process parameters in PPD pixel design on the potential barrier and pocket is clarified. The whole study help improve the understanding of the charge transfer limitation mechanism, and can achieve high charge transfer efficiency and low image lag noise in the PPD pixel design of CMOS image sensors (CISs).